A revised dated phylogeny of the arachnid order Opiliones - Sharma, Prashant P.; Giribet, Gonzalo (Frontiers in Genetics, 2014)
Dating the Opiliones tree of life has become an important enterprise for this group of arthropods, due to their ancient origins and important biogeographic implications. To incorporate both methodological innovations in molecular dating as well as new systematic discoveries of harvestman diversity, we conducted total evidence dating on a data set uniting morphological and/or molecular sequence data for 47 Opiliones species, including all four well-known Palaeozoic fossils, to test the placement of both fossils and newly discovered lineages in a single analysis. Furthermore, we investigated node dating with a phylogenomic data set of 24,202 amino acid sites for 14 species of Opiliones, sampling all extant suborders. In this way, we approached molecular dating of basal harvestman phylogeny using different data sets and approaches to assess congruence of divergence time estimates. In spite of the markedly different composition of data sets, our results show congruence across all analyses for age estimates of basal nodes that are well constrained with respect to fossil calibrations (e.g., Opiliones, Palpatores). By contrast, derived nodes that lack fossil calibrations (e.g., the suborders Cyphophthalmi and Laniatores) have large uncertainty intervals in diversification times, particularly in the total evidence dating analysis, reflecting the dearth of calibration points and undersampling of derived lineages. Total evidence dating consistently produced older median ages than node dating for ingroup nodes, due to the nested placement of multiple Palaeozoic fossils. Our analyses support basal diversification of Opiliones in the Ordovician-Devonian period, corroborating the inferred ancient origins of this arthropod suborder, and underscore the importance of diversity discovery—both paleontological and neontological—in evolutionary inference.